Kajian Pembelajaran Higher Order Thinking Skills (Hots) - Hayumuti, Hayumuti (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2018)
Abstract: The purpouse of this journal is to examine the learning of higher order thinking skills. Finding out whether there are differences in perceptions regarding higher order thinking skills in terms of areas of study, teaching experience, geographical areas and school locations. It also reviews the constraints of a lack of knowledge from edycators, who lack of knowledge from educators. Who lack undertanding of strategies, lack of materials and references for teaching that are inadequate and also the setting of an environment that is not ppropriate for instilling higher order thinking skills learning. Teachers often face a certain level of difficulty in facilitating students to achieve certain competencies. The factors that cause difficulties can be from the teacher, facilities, and students. Often a variety of strategies develop by others cannot be used by teachers in overcoming problems in their classrooms. This problem is because the caracteristics of each child who joins the study group are very specific Key Words : Pembelajaran Higher Order Thinking